2007
DOI: 10.4067/s0301-732x2007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de concentraciones elevadas de sales totales y sulfatos en agua de bebida sobre la degradabilidad ruminal in vitro de Thinopyrum ponticum

Abstract: Efecto de concentraciones elevadas de sales totales y sulfatos en agua de bebida sobre la degradabilidad ruminal in vitro de Thinopyrum ponticum Effect of drinking water with high concentrations of total salts and sulphates on in vitro ruminal degradability of Thinopyrum ponticum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Water is an essential nutrient for the growth and well-being of livestock (Beede, 2005;Huuskonen et al, 2011), as poor-quality drinking water has been shown to affect animal health and productive performance (NRC, 2005;Brew et al, 2008). Results of previous studies have demonstrated that poor-quality drinking water affects water intake (Socha et al, 2003;Grout et al, 2006;Sharma et al, 2017), feed intake (Ru et al, 2004;Umar et al, 2014;López et al, 2016), average daily weight gain [ADG] (Lardner et al, 2005;Waldner and Looper, 2007;Sharma et al, 2017), milk production (Solomon et al, 1995;Shapasand et al, 2010), and ruminal conditions (Coria et al, 2007;Valtorta et al, 2008). In addition, poorquality drinking water favors diseases (Gould, 1998) and pathogen incidence in the digestive tract of dairy cows (LeJeune et al, 2001;Brew et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Water is an essential nutrient for the growth and well-being of livestock (Beede, 2005;Huuskonen et al, 2011), as poor-quality drinking water has been shown to affect animal health and productive performance (NRC, 2005;Brew et al, 2008). Results of previous studies have demonstrated that poor-quality drinking water affects water intake (Socha et al, 2003;Grout et al, 2006;Sharma et al, 2017), feed intake (Ru et al, 2004;Umar et al, 2014;López et al, 2016), average daily weight gain [ADG] (Lardner et al, 2005;Waldner and Looper, 2007;Sharma et al, 2017), milk production (Solomon et al, 1995;Shapasand et al, 2010), and ruminal conditions (Coria et al, 2007;Valtorta et al, 2008). In addition, poorquality drinking water favors diseases (Gould, 1998) and pathogen incidence in the digestive tract of dairy cows (LeJeune et al, 2001;Brew et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Por esta razón, el ganado mayormente vacuno puede ser abastecido con agua con un tenor salino más alto, tal como la relevada en la antigua llanura de marea o en los lunettes. En estas áreas el agua determinada fue principalmente de tipo clorurada sódica, la cual no afectaría a la salud del ganado, que se ve afectado cuando el agua se torna sulfatada, ocasionando la pérdida de peso por diarrea y la deshidratación del animal (Sager, 2000;Bavera et al, 2001;Coria et al, 2007).…”
Section: Viii-2 Reservas De Agua Dulceunclassified